Irish Red - Kjelgaard, Jim. (New York : Bantam, 1984)
After many misadventures, a rebellious Irish setter finally proves that he can act like the thoroughbred he is. Sequel to "Big Red."
School Library Journal starred
School Library Journal
Booklist
6.1
5-8
Keywords: Dogs -- Fiction; Dogs -- Fiction